Triboelectric signal generation and its versatile utilization during gear-based ordinary power transmission. (July 2020) - Ra, Yoonsang; Oh, Seungin; Lee, JoonHo; Yun, Yeongcheol; Cho, Sumin; Choi, Jun Hyuk; Jang, Sunmin; Hwang, Hee Jae; Choi, Dukhyun; Kim, Jin-Gyun; Choi, Dongwhi
Abstract: Gear is one of the most ordinary and effective components for transmitting mechanical power and thus, it has been used in various industrial fields as a core component of machines. In this paper, the mechanism of triboelectric signal generation during gear-based ordinary power transmission is firstly proposed. The signal generation mechanism during contact and separation of engaged gear teeth is verified by intensive analytical, numerical as well as experimental analyses. Given that the remarkable amount of the electric signal can be periodically generated during its operation, the generated signal can be utilized to develop a real-time and self-triggered gear-based power transmission monitoring system, which is simple, cost-effective and user-friendly compared to the other existing methods. Beyond detecting the electric signals, a binary code generator is established using the change in signals. Furthermore, scavenging the spontaneously generated triboelectric signals while operating the gearbox enables us to advantageously utilize wasted energy. The simple electronic devices such as Bluetooth based wireless thermo-hygrometer, calculator and custom-built LED display with more than 100 LEDs can be sufficiently operated by using the wasted energy that is easily harvested during ordinary power transmission. Graphical abstract: Image 1 Highlights: Proposal of triboelectric signal generation with gear-based ordinary power transmission. Analytical, numerical and experimental Intensive analyses on triboelectric signal generation. Development of a real-time and self-triggered gear status monitoring system. Energy harvesting during gear-based ordinary power transmission.